Grain waste processing in Ukraine and EU countries based on circular economy principles - Rudnytsky, Ivan; Yastremska, Larysa; Huliaiev, Vitalii; Korniienko, Iryna; Anatskyi, Andrii; Kovalenko, Alla; Korniienko, Yurii; Filimonenko, Olha (Problems of Environmental Biotechnology, 2024)
The issue of grain waste processing in Ukraine and EU countries based on the principles of circular economy is considered